Integrative analysis of gene expression profiles reveals specific signaling pathways associated with pancreatic duct adenocarcinoma. Issue 1 (27th April 2018) - Li, Jun; Tan, Wenle; Peng, Linna; Zhang, Jialiang; Huang, Xudong; Cui, Qionghua; Zheng, Jian; Tan, Wen; Wu, Chen; Lin, Dongxin
Abstract: Background: Pancreatic duct adenocarcinoma (PDAC) remains a major health problem because conventional cancer treatments are relatively ineffective against it. Microarray studies have linked many genes to pancreatic cancer, but the available data have not been extensively mined for potential insights into PDAC. This study attempted to identify PDAC‐associated genes and signaling pathways based on six microarray‐based profiles of gene expression in pancreatic cancer deposited in the gene expression omnibus database. Methods: Pathway network methods were used to analyze core pathways in six publicly available pancreatic cancer gene (GSE71989, GSE15471, GSE16515, GSE32676, GSE41368 and GSE28735) expression profiles. Genes potentially linked to PDAC were assessed for potential impact on survival time based on data in The Cancer Genome Atlas and International Cancer Genome Consortium databases, and the expression of one candidate gene ( CKS2 ) and its association with survival was examined in 102 patients with PDAC from our hospital. Effects of CKS2 knockdown were explored in the PDAC cell lines BxPC‐3 and CFPAC‐1. Results: The KEGG signaling pathway called "pathway in cancer" may play an important role in pancreatic cancer development and progression. Five genes ( BIRC5, CKS2, ITGA3, ITGA6 and RALA ) in this pathway were significantly associated with survival time in patients with PDAC. CKS2 was overexpressed in PDAC samples from our hospital, and higher CKS2 expression in these patients was associated with shorter survival time. CKS2 knockdown substantially inhibited PDAC cell proliferation in vitro. Conclusions: Analysis integrating existing microarray datasets allowed identification of the "pathway in cancer" as an important signaling pathway in PDAC. This integrative approach may be powerful for identifying genes and pathways involved in cancer.